Credit Agreement Due To The Corona-19 Pandemic (Study of Wonosari District Court Decision Number 3/Pdt.G.S/2020) - Pani Chadijah Nasution; Surya Perdana; Muhammad Arifin (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2022)
The corona pandemic as a delay in credit payments, the determination of the non-natural disaster Covid-19 as a national disaster through Presidential Decree 12/2020 does not automatically become the basis for parties in commercial agreements to declare themselves in a state of force majeure. In-depth study of case by case analysis by paying attention to the clauses in an agreement becomes the benchmark for determining the state of force majeure. As a result of parties who did not fulfill their achievements in the credit agreement during the Covid-19 period. The suspension of liability occurs when a force majeure event is temporary. When the condition of the obstacle has recovered, for example the export ban is lifted again, then the obligation of the seller returns to recover to hand over the exported goods. Agreement resulting from the corona 19 pandemic in the perspective of presidential decree no. 12 of 2020 concerning the determination of non-natural disasters (Wonosari State Court Decision Study Number 3 / Pdt.G.S / 2020) in agreements usually also regulates the consequences of a force majeure event, for example whether to postpone an agreement or can be used as a condition for canceling an agreement